Environmental Education in the Science Curriculum in Different Countries: Turkey, Australia, Singapore, Ireland, and Canada - Mustafa Derman; Hasan Gurbuz (Seyit Ahmet Kıray, 2018)
This study aimed to compare the objectives of environmental education topics in various countries. The present study is a qualitative study and content analysis was used to analyze the data. The results revealed that the categories of the objectives regarding the environment topic in the primary education were found to be higher in Turkey compared to other countries. The concept of the ozone layer in chemistry curricula and the concept of biodiversity in biology curricula were intensively included. No country had objectives regarding all subcategories in primary education. There are no objectives regarding field trip in physics subject in all countries. Objectives regarding the category of identifying issues and research question were included only in Australia. However, the activities for environmental education were determined to be at a low level in all the countries.